KECERDASAN EMOSIONAL DAN TEACHER EFFICACY PADA SEKOLAH DASAR DENGAN KURIKULUM 2013 - FITRI LESTARI ISSOM; ALSYAMENTI YORANI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
This study aims to research determine the effect of emotional intelligence against teacher efficacy in elementary school with curicullum 2013. Variable studied were emotional intelligence as the independent variable (X) and variable teacher efficacy as the dependent variable. The method used in this study is quantitative research with technique cluster sampling. The sample in this study amounted to 50 respondents. The data analysis technique are used to test the hypotesis is a simple regresission analysis using Rasch Model with winstep version 3.73 and SPSS version 16.0. Based on the calcullations, emotional intelligence effects teacher efficacy by 6% and the remaining 94% is in influenced by factors other than emotional intelligence.